2007
DOI: 10.3998/ark.5550190.0008.c09
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of rapamycin and its ring-opened isomer: Role of base catalysis

Abstract: Rapamycin is a natural macrolide immunosuppressant with a distinct mechanism of action. Quantitative analysis of rapamycin poses many challenges associated with facile degradation and the multitude of isomeric forms. The primary goal of this study was to compare degradation of rapamycin and its ring-opened isomer, secorapamycin, in aqueous solution under identical conditions. Reaction kinetics and mechanisms were studied in 30/70 vol/vol acetonitrile-water mixtures containing either MeCOONH 4 (apparent pH 7.3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Comparable seco-species are a well-known degradant from rapamycin itself (where it is known as secorapamycin 34), which forms in vivo, 91,92 under enzymatic processes (CYP 3A4) 89,90 and under basic conditions. 72,74,75 Testing of the seco-products 32 and 33, formed from bi-steric inhibitors 16 and 30, respectively, indicated that they were much less potent as mTORC1 or mTORC2 inhibitors (Table 4). Due to the prevalence of a seco-product when bi-steric inhibitors containing a C32 carbonyl were dosed to rodents or when subjected to mildly basic conditions (Scheme 3), we sought to prepare additional compounds that would be less susceptible to forming a ring-opened degradant.…”
Section: ■ Chemistrymentioning
confidence: 99%
“…Comparable seco-species are a well-known degradant from rapamycin itself (where it is known as secorapamycin 34), which forms in vivo, 91,92 under enzymatic processes (CYP 3A4) 89,90 and under basic conditions. 72,74,75 Testing of the seco-products 32 and 33, formed from bi-steric inhibitors 16 and 30, respectively, indicated that they were much less potent as mTORC1 or mTORC2 inhibitors (Table 4). Due to the prevalence of a seco-product when bi-steric inhibitors containing a C32 carbonyl were dosed to rodents or when subjected to mildly basic conditions (Scheme 3), we sought to prepare additional compounds that would be less susceptible to forming a ring-opened degradant.…”
Section: ■ Chemistrymentioning
confidence: 99%
“…Values of observed rate constants(k obs ) of tacrolimus in HPβCD solution at pH 5 and 9 with and without 0.1% EDTA. compounds, like everolimus and sirolimus, where the lactone group is hydrolyzed as explained byIl'ichev et al (Il'ichev et al, 2007) (Nogueiras-Nieto, 2012. Another less polar compound was obtained at 4.38 RT with m/z 808.…”
mentioning
confidence: 99%
“…Third, the aqueous solution containing Tween-20 was used as the in vitro release medium. Sirolimus is very unstable in various aqueous solutions and has poor water solubility [ 58 , 59 , 60 , 61 ]. According to our previous work, the aqueous solution was supplemented by Tween-20 (4 g/L) to increase the stability and solubility of sirolimus, thereby attaining a favorable sink condition for the sirolimus release experiments [ 62 ].…”
Section: Resultsmentioning
confidence: 99%